PENGARUH KONSENTRASI KITOSAN DAN LAMA SIMPAN TERHADAP PERTUMBUHAN AWAL DAN KUALITAS BIBIT TEBU (Saccharum officinarum L.) MATA TUNAS TUNGGAL - , MARDIANA AGUSTIN, Dr. Ir. Taryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One effort to increase sugarcane productivity is the availability of good seed. Bud chips are the alternative planting materials that are more efficient and economic in term seed cane transport, but there are various limitations such as low nutrient reserves and injury tissue therefore the percentage of seed germination decreased drastically if they are not planted immediately. This research aimed to know the effect of chitosan application and storage longevity on the quality and early growth seed cane bud chip seedlings (Saccharum officinarum L.). This research arranged according to completely randomized design (CRD) 5 x 5 factorial with four replications. The first factor was storage period i.e. 0 (not stored), 5, 10, 15, and 20 days, whereas the second factor was concentrations of chitosan i.e. 0 (soaked fungicide 4 g/l), 1, 2, 3, and 4 g/ml. The results showed that the quality and early seedling growth of seed cane bud chips decreased during storage. There was an interaction between concentrations of chitosan and storage period on weight loss, percentage of pathogen attack, percentage of bud chips mortality, percentage of rooted bud chips, percentage of seed germination, vigor index, plant height at 8 week after planting, number of leaf at 8 WAP, fresh and dry shoot weight, fresh and dry roots weight, root volume, and total root length, but there was no interaction on stem diameter at 8 WAP and number of tillers. The quality and early seedling growth of sugar cane bud chips can still be maintained up to 10 days of storage with 3 - 4 g/ml chitosan coating as indicated by percentage of germination and seedling growth of cane at the age of 8 WAP.